Pengaruh Fasilitas Kinerja dan Lingkungan Kerja terhadap Kinerja Pegawai Kantor Pemadam Karawang - Heryanto, Heryanto; Suroso, Suroso; Maman Mulya Karnama (Journal of Management and Bussines (JOMB), 2025)
This study aims to explain the influence of Facilities and Work Environment on the Performance of Employees at the Karawang Fire Department. This study uses Verification, the sample in this study was 42 respondents, a saturated sample type, taking all populations as samples. Data were obtained using a liket-scale questionnaire distributed using Google Form. The data analysis method used Multiple Linear Regression Analysis using the SPSS V16 tool. The results of this study indicate that the Facility Variable partially has a positive and significant effect on Employee Performance and the Work Environment partially has a positive and significant effect on Employee Performance. Work Facilities and Work Environment simultaneously have a positive and significant effect on Employee Performance at the Karawang Fire Department.   Keywords : Facilities, Environment, Performance, Office